Quality assessment of fresh pork sausages(chorizo) produced in Iloilo City - Yazon,Frisian C. (2001.)
The microbiological quality and chemical safety of fresh pork sausages, obtained from five local manufacturers (identifieed as A,B,C, D, and E) in Iloilo City were analyzed.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Fresh pork sausages; Chorizo